Short Bowel Syndrome: Surgical Therapy - W Donald Buie; Olin G Thurston; Richard N Fedorak (Canadian Journal of Gastroenterology)
Many surgical solutions to short bowel syndrome have been proposed; however, none has proven to be uniformly successful. Some of these solutions, combined with optimal medical management, may represent the patient's only hope for survival without parenteral nutrition. Most forms of surgical therapy are supportive and aim at controlling three basic pathophysiological defects: decreased intestinal transit time, gastric hypersecretion, and reduced functional mucosal surface area. Conservative resection and, thus, prevention of short bowel syndrome remains the best form of treatment at present. In the future, small bowel transplantation may prove to be an important advance in therapy; however, this remains largely experimental due to continued problems with rejection.